Micronutrient fortification of plants through plant breeding: can it improve nutrition in man at low cost? - Bouis, Howarth E. (Cambridge University Press, 2003)
Can commonly-eaten food staple crops be developed that fortify their seeds with essential minerals and vitamins? Can farmers be induced to grow such varieties? If so, would this result in a marked improvement in human nutrition at a lower cost than existing nutrition interventions? An interdisciplinary international effort is underway to breed for mineral- and vitamin-dense varieties of rice, wheat, maize, beans and cassava for release to farmers in developing countries. The biofortification strategy seeks to take advantage of the consistent daily consumption of large amounts of food staples by all family members, including women and children as they are most at risk for micronutrient malnutrition. As a consequence of the predominance of food staples in the diets of the poor, this strategy implicitly targets low-income households. After the one-time investment is made to develop seeds that fortify themselves, recurrent costs are low and germplasm may be shared internationally. It is this multiplier aspect of plant breeding across time and distance that makes it so cost-effective. Once in place, the biofortified crop system is highly sustainable. Nutritionally-improved varieties will continue to be grown and consumed year after year, even if government attention and international funding for micronutrient issues fades. Biofortification provides a truly feasible means of reaching malnourished populations in relatively remote rural areas, delivering naturally-fortified foods to population groups with limited access to commercially-marketed fortified foods that are more readily available in urban areas. Biofortification and commercial fortification are, therefore, highly complementary. Breeding for higher trace mineral density in seeds will not incur a yield penalty. Mineral-packed seeds sell themselves to farmers because, as recent research has shown, these trace minerals are essential in helping plants resist disease and other environmental stresses. More seedlings survive and initial growth is more rapid. Ultimately, yields are higher, particularly in trace mineral-‘deficient’ soils in arid regions.